2009
DOI: 10.2214/ajr.08.1752
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Metastasis From Hepatocellular Carcinoma: Radiofrequency Ablation Combined With Adrenal Arterial Chemoembolization in Six Patients

Abstract: The combination therapy described is a safe multidisciplinary therapeutic option that can lengthen survival among patients with adrenal metastasis from hepatocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 27 publications
2
50
0
Order By: Relevance
“…Our current analyses indicated that resection of metastatic lesions produced a satisfactory local response, consistent with previous reports. [32][33][34][35][36] Locoregional therapy for extrahepatic metastasis also was discussed in earlier studies, including irradiation for bone, 37 lymph node, 38 brain, 39 and adrenal 40 metastases; TACE for adrenal metastasis 41 ; and percutaneous ablation for adrenal 42 and bone metastases. 43 We also used these methods to treat some patients in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Our current analyses indicated that resection of metastatic lesions produced a satisfactory local response, consistent with previous reports. [32][33][34][35][36] Locoregional therapy for extrahepatic metastasis also was discussed in earlier studies, including irradiation for bone, 37 lymph node, 38 brain, 39 and adrenal 40 metastases; TACE for adrenal metastasis 41 ; and percutaneous ablation for adrenal 42 and bone metastases. 43 We also used these methods to treat some patients in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Yamakado et al 75 reported on 6 patients with 8 adrenal HCC metastases that were managed with combinedmodality therapy. All patients either were not surgical candidates or refused surgery.…”
Section: Arterial Embolizationmentioning
confidence: 99%
“…Treatments for adrenal metastases and otherwise limited metastatic disease were previously limited to adrenalectomy, radiofrequency ablation (RFA), transcatheter arterial chemoembolization (TACE), or systemic therapy (3,4). In a metaanalysis of 114 patients with non-small cell lung cancer undergoing resection of adrenal metastases, the 5-year overall survival was 25-26%, suggesting that there can be long-term survivors in this group of patients (5).…”
Section: Introductionmentioning
confidence: 99%